PECULIARITIES OF TRANSLATION OF POLITICAL TEXTS IN SIMULTANEOUS INTERPRETATION - Aslonov, Shahram; Saidova, Marjona (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Simultaneous interpretation of political texts presents a unique set of challenges and intricacies, requiring interpreters to navigate not only linguistic differences but also cultural nuances, political ideologies, and sensitive diplomatic relations. This demanding task demands a high level of skill, concentration, and cultural sensitivity from interpreters. This article explore some aspects of translating political texts in simultaneous translation.